Book Review: Himanshu Roy, Mahendra Prasad Singh and A. P. S. Chauhan (eds.), State Politics in India. (December 2018) - Harriss, John
Himanshu Roy, Mahendra Prasad Singh and A. P. S. Chauhan (eds.), State Politics in India . New Delhi: Primus Books. 2017. 931 pages. ₹2095.